Effects of domestic air travel on technical and tactical performance and recovery in soccer - Fowler, P.; Duffield, R.; Vaile, J. (International Journal of Sports Physiology and Performance, 2014)
The current study examined the effects of short-haul air travel on competition performance and subsequent recovery. Six male professional Australian football (soccer) players were recruited to participate in the study. Data were collected from 12 matches, which included 6 home and away matches against the same 4 teams. Together with the outcome of each match, data were obtained for team technical and tactical performance indicators and individual player-movement patterns. Furthermore, sleep quantity and quality, hydration, and perceptual fatigue were measured 2 days before, the day of, and 2 days after each match. More competition points were accumulated (P > .05, d = 1.10) and fewer goals were conceded (P > .05, d = 0.93) in home than in away matches. Furthermore, more shots on goal (P > .05, d = 1.17) and corners (P > .05, d = 1.45) and fewer opposition shots on goal (P > .05, d = 1.18) and corners (P < .05, d = 2.32) occurred, alongside reduced total distance covered (P > .05, d = 1.19) and low-intensity activity (P < .05, d = 2.25) during home than during away matches. However, while oxygen saturation was significantly lower during than before and after outbound and return travel (P < .01), equivocal differences in sleep quantity and quality, hydration, and perceptual fatigue were observed before and after competition away compared with home. These results suggest that, compared with short-haul air travel, factors including situational variables, territoriality, tactics, and athlete psychological state are more important in determining match outcome. Furthermore, despite the potential for disrupted recovery patterns, return travel did not impede player recovery or perceived readiness to train.